2007
DOI: 10.1002/ajim.20536
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence and mortality in a Swedish rubber tire manufacturing plant

Abstract: The finding of an excess of tumors in the respiratory system is in agreement with earlier findings in other studies on rubber tire workers. The results on other cancer types are compared to earlier findings and related to work processes and chemical exposures of possible causal importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 37 publications
1
14
0
3
Order By: Relevance
“…The IARC acknowledged an increased risk of skin cancer in 1982, also noting that lubricating oils in uncured rubber contain known skin carcinogens [ 1 ]. However, a more recent Swedish study conducted in 2007 examined 5,745 rubber workers and failed to demonstrate increased risk of skin cancer in the rubber industry [ 20 ]. In 2012, the IARC concluded that there is insufficient evidence to determine the relationship between the rubber industry and skin cancer [ 5 ].…”
Section: Cutaneous Manifestations Of Occupational Exposure In the Rubmentioning
confidence: 99%
See 1 more Smart Citation
“…The IARC acknowledged an increased risk of skin cancer in 1982, also noting that lubricating oils in uncured rubber contain known skin carcinogens [ 1 ]. However, a more recent Swedish study conducted in 2007 examined 5,745 rubber workers and failed to demonstrate increased risk of skin cancer in the rubber industry [ 20 ]. In 2012, the IARC concluded that there is insufficient evidence to determine the relationship between the rubber industry and skin cancer [ 5 ].…”
Section: Cutaneous Manifestations Of Occupational Exposure In the Rubmentioning
confidence: 99%
“…Well-documented associations of cancer in the rubber industry related to specific occupational exposures include the excess risk of leukemia with benzene exposure [ 20 , 21 ], bladder cancer with 2-naphthylamine [ 22 ] and o-toluidine exposure [ 23 ], lung cancer with asbestos and carbon black [ 24 ], and nitrosamines released during vulcanization posing excess risk of pharyngeal, esophageal and cancers of the oral cavity [ 25 ]. This distinction highlights the importance of understanding worker duties and exposures when advising industrial rubber workers about cancer risk.…”
Section: Cancers Other Than Skinmentioning
confidence: 99%
“…Los resultados de esta revisión verifican la asociación (causa-efecto) entre la exposición a determinados agentes químicos y el cáncer de piel en el ámbito laboral. Los agentes causales más referenciados fueron plaguicidas [22][23][24][25] y componentes derivados del petróleo [26][27][28][29][30][31] , como los hidrocarburos aromáticos policíclicos (PAHs).…”
Section: Discusión Y Conclusionesunclassified
“…En los trabajadores de neumáticos que empleaban entre otros hidrocarburos aromáticos policíclicos se encontró una disminución de los riesgos de incidencia para el cáncer de piel 29 . Coincide con la decisión en 1982 de la IARC según la cual no existen pruebas suficientes de que trabajar en la industria del caucho conlleve un riesgo de cáncer [IARC, 1987].…”
Section: Discusión Y Conclusionesunclassified
“…Most of the data on carcinogenic risk in the rubber industry come from the studies that have been carried out in factories in the United States and Western Europe [14][15][16][17][18][19][20][21][22][23][24][25][26][27], with only few studies being conducted in other parts of the world [28][29][30]. In Poland a retrospective cohort study of rubber workers employed after 1950 was set up in the early 1990s with the results published for the first time in 2001 [30] after a follow-up until 1995.…”
Section: Introductionmentioning
confidence: 99%